DEVONIAN CONODONTS FROM SPITI HIMALAYA, INDIA (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2023)
The present paper describes the lower Upper Devonian conodont fauna from the upper units of Muth Formation, Spiti Valley, Himalaya.
Keywords: Conodonta; Biostratigraphy; Chronostratigraphy; Devonian; Himalaya .